Human impacts on pasture degradation (A case study of the Dornod, Sukhbaatar, Khentii provinces) - Tseren, Narantsatsral; Ganbat, Danzanchadav; Purevsuren, Telmen; Mandakh, Urtnasan; Tsevelmaa, Ikhbayar (Mongolian Journal of Geography and Geoecology, 2025)
As Mongolia transitioned to a market economy, rapid population and economic growth have spurred human settlements and significant urbanisation. Over the last two decades, Mongolia’s population has increased by 1 million and livestock numbers have soared by over 30 million. This growth, coupled with the expansion of urban areas and road networks, has intensified pressure on land resources, leading to degradation. Notably, pastureland constitutes over 80 percent of Mongolia's total land area. This study aims to identify and map the human impacts contributing to pasture degradation in Mongolia’s eastern regions, i.e., Dornod, Sukhbaatar, and Khentii provinces. We developed a map that illustrates these human impacts by considering eight factors rooted in recent research and the particular land use characteristics of Mongolia. These factors include the proximity of wells, rivers and lakes, winter and spring camps, road networks, settlement areas, mining areas, cropland, and livestock density. To assess the human impacts, we produced individual maps for each of the eight selected factors, culminating in a comprehensive assessment map. Our findings reveal that 12.6 percent of the eastern region, equivalent to 3,607 thousand hectares, remains unaltered by human activities. In contrast, 62 percent of the region (17,742 thousand hectares) experiences low impact, 24.2 percent (6,935 thousand hectares) encounters moderate impact, and 1.2 percent (337 thousand hectares) is highly affected by human activities.